Strategy For Developing a Cultural Dance Studio as A Leading Tourism Attraction - Any Nurcholiyah; Sri Rahayu; Untung Tamsil (Journal of Business Innovation and Accounting Research, 2024)
The research delves into the strategic implementation necessary for cultivating Papuan traditional dance arts and cultural tourism in the Fakfak district, aiming to elevate it as a premier tourism attraction. Utilizing an empirical research methodology grounded in factual evidence, the study involves meticulous field observations aligned with the researcher's core duties, enriched by insights from Fakfak Regency Government policymakers and academia. The findings underscore the imperative for concerted and rigorous efforts by the Fakfak Regency Government and stakeholders to foster dance and cultural arts, positioning them as a key tourist draw. The study identifies ancillary services, accommodation, and creativity as critical areas requiring urgent intervention. These elements represent the primary challenges deterring tourism businesses from marketing Fakfak as a destination, due to concerns over inadequacy in fulfilling tourist expectations and enhancing the overall visitor experience. Addressing these weaknesses is crucial for unlocking Fakfak’s potential as a cultural tourism hotspot. This entails developing robust infrastructure, fostering innovation in tourism offerings, and ensuring high standards of hospitality. Such strategic initiatives are vital for transforming Fakfak into an attractive and competitive destination within the global tourism landscape, ultimately contributing to regional development and cultural preservation.